(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Prolactinomas are first-line drug treatment, which in most cases is required in optimal doses to achieve treatment goals, and this dose has also been shown to be safe; however, in patients in whom no response is evidenced, raising the dose may be considered for the drug to be effective and this population will probably be more prone to developing adverse effects. Objective: To determine the efficacy of cabergoline in the management of prolactinoma. Materials and methods: retrospective, descriptive, comparative, observational, longitudinal study, of 42 patients with prolactinomas treated at the "Hospital de Especialidades Guayaquil, Doctor Abel Gilbert Pontón", in the period January to September 2020, data management was performed in sheets Microsoft Excel 2010 calculation program, where data processing was performed and the SPSS version 23 program was used for statistical analysis. Results: 100% received cabergoline, 19% required doses greater than 2mg / week, demonstrating clinical benefit, especially with cabergoline alone and in low doses except for visual field alterations, the normalization of prolactin was achieved in 81%, the majority with low doses, the reduction of tumor size occurred in 100% of the patients, being effective all the schemes of Treatment studied, 17% presented adverse effects and most were resolved, no valvular disease was evident. Conclusions: Cabergoline therapy in the management of prolactinomas is effective and safe in low doses.